E-2: HOW SOCIETAL AND INDIVIDUAL DIVERSITY AFFECT BRAND EQUITY OF HIGH VERSUS LOW INVOLVEMENT PRODUCTS AND MEDIATING ROLE OF SOCIAL VALUE AND CONTENT VALUE - Mohiy Uddin; Siddiqui, Danish Ahmed (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2024)
Digitalization has influenced the marketing function of various businesses. It helps in the promotion of their products internationally resulting in increased sales and development of community on social media than traditional medium. The formation of social media-based communities is debatable because some scholars think it provides relationship-building opportunities to companies while few have the opposite opinion. Considering this viewpoint, the paper’s objective is to explore how societal and individual diversity impact brand equity of high versus low involvement products and the mediating role of social value and content value. The survey is carried out among 600 social media-based community members in Karachi. Smartpls is used for data analysis. The result verifies that buyers having extrinsic, extroversion, and collectivist characteristics prefer social value. Whereas, buyers with intrinsic, introversion, and individualism qualities like the content value on social media-based community. These values have a significant direct and mediating impact on brand equity and its dimensions under investigation. So organizations can persuade buyers to enjoy these values by taking part in the social media-based community and developing a diversified environment that facilitates cultural exchange and making powerful brand equity and its dimensions under study.